(untitled) (PANGEEA, 2025)
The aim of the paper is to illustrate necessary and current stages of modern archaeology by using techniques and methods specific to archaeological topography and Geographic Information Systems, which play an important role both in generating and structuring entities of archaeological interest, and in developing a three-dimensional model of the surrounding area.